Manajemen Pendidikan Inklusif Berbasis Nilai-Nilai Islam: Strategi Pengembangan Kurikulum dan Fasilitas Untuk Mendukung Keberagaman Peserta Didik - Apriyadi, Ridho; Septia, Rizka; Hidayat, Taufik; Elistatia, Usi; Junaidah, Junaidah; Abdurahman, Abdurahman (Indonesian Journal of Islamic Educational Management, 2024)
The objective of this study is to develop a curriculum and educational facilities based on Islamic values to support student diversity in inclusive schools. The main issue addressed is how to integrate Islamic values into inclusive education management to create a learning environment responsive to the needs of all students, including those with special needs. This research was conducted qualitatively through a case study, with data collected through observations, interviews, and document analysis. Data analysis was performed using thematic analysis to identify patterns, themes, and relationships within the collected data. Observation data were utilized to describe the dynamics of interactions in inclusive school environments, while interview data provided in-depth insights into the perceptions of teachers, students, and parents regarding the implementation of Islamic values in inclusive education. Document analysis involved reviewing school policies, curricula, and other supporting documents to understand the extent to which Islamic values are integrated into inclusive education management. The results indicate that the implementation of Islamic values in inclusive education management can enhance mutual respect and openness among students, resulting in an inclusive and harmonious learning atmosphere. Two key components that significantly contribute to the successful implementation of Islamic-based inclusive education are the development of a flexible curriculum and the provision of a supportive environment for diversity